Kret yo̜i rō̜i rư̄ang chabap prapprung læ phœ̄mtœ̄m - Sombat Phlāinō̜i (Sathāphō̜n Buk, 2021)
100 short articles about various subjects of Thai culture, history and art Collection of short articles on culture, history, traditions, and food of Thailand
Keywords: Aufsatzsammlung